1999
DOI: 10.1103/physrevd.60.067502
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic curvature of the BTZ black hole

Abstract: In this paper we apply the concept of thermodynamic geometry to the Bañados-Teitelboim-Zanelli ͑BTZ͒ black hole. We find the thermodynamic curvature diverges at the extremal limit of the black hole, which means the extremal black hole is the critical point with the temperature zero. We also study the effective dimensionality of the underlying statistical model. Near the critical point, the picture is clear; the spatial dimension of the underlying statistical model is just one, which agrees with other results. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 35 publications
(49 reference statements)
4
117
0
Order By: Relevance
“…The third singularity located at ln r + = 0 can be interpreted as a critical point that is not determined by the heat capacity (19). In fact, at r + = 1 the second derivative of the mass ∂ 2 M/∂Q 2 = 0, indicating either the transition into a region of instability or a second order phase transition.…”
Section: Geometrothermodynamics Of the Cr-btz Black Holementioning
confidence: 99%
See 2 more Smart Citations
“…The third singularity located at ln r + = 0 can be interpreted as a critical point that is not determined by the heat capacity (19). In fact, at r + = 1 the second derivative of the mass ∂ 2 M/∂Q 2 = 0, indicating either the transition into a region of instability or a second order phase transition.…”
Section: Geometrothermodynamics Of the Cr-btz Black Holementioning
confidence: 99%
“…Nevertheless, a change of the thermodynamic potential affects the Ruppeiner geometry in such a way that the resulting curvature singularity does not correspond to a phase transition. Another example is provided by the Bañados-Teitelboim-Zanelli (BTZ) black hole thermodynamics for which the curvature of the equilibrium space turns out to be flat [19][20][21]. This flatness is usually interpreted as a consequence of the lack of thermodynamic interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, applying the thermodynamical geometry to black hole thermodynamics was initiated in [58], there it was found that the Weinhold metric is proportional to the metric on the moduli space for supersymmetric extremal black holes, whose Hawking temperature is zero, and the Ruppeiner metric governing fluctuations naively diverges, which is consistent with the argument that near the extremal limit, the thermodynamical description breaks down. Applying the thermodynamical geometry approach to phase transition of black holes was followed in [59][60][61], and for more relevant references see the recent review [62] and references therein. In particular, refs.…”
Section: Jhep02(2015)143mentioning
confidence: 99%
“…The Riemannian-geometric approach to thermodynamics has been applied to a variety of systems, among which black holes stand out (this approach to black hole thermodynamics was pioneered by Cai et al [16]). The purpose of this viewpoint is twofold: on the one hand, it intends to relate the divergences of heat capacities (often regarded as thermodynamic critical points) to geometric singularities of Weinhold's metric structure; on the other, it is aimed to determine the nature of the interactions involved in microscopic models of gravity via Ruppeiner's conjecture.…”
Section: Introductionmentioning
confidence: 99%